Plastic Moment of Intermediate Horizontal Boundary Elements of Steel Plate Shear Walls - Bruneau, Michel; Qu, Bing (Engineering Journal, 2011)
This paper presents results of an analytical study of plastic moment in horizontal boundary elements (HBEs) in steel plate shear walls. To account for the effect of shear and vertical stresses in HBE web, the reduced axial yield strength was studied using the von Mises yield criterion. In the spirit of classic plastic analysis, analytical procedures for estimating plastic moment of the intermediate HBE under equal top and bottom tension fields are developed. Those analytical procedures are then extended for intermediate HBE under unequal top and bottom tension fields. Both positive and negative flexures are considered. Results from the analytical procedures are shown to agree well with those from finite element analysis. Simplified models for estimating plastic moment of HBEs are also developed for design and shown to be accurate.